Aryl isoprenoids and their significance for inter-salt shale oil exploration in the Jianghan Basin - Xiaoxiao MA; Maowen LI; Peng LIU; Zhiming LI; Qigui JIANG; Guoliang TAO; Menhui QIAN; Yunjie BAO; Tingting CAO; Shiqiang WU (Shiyou shiyan dizhi, 2020)
Fifteen inter-salt shale cores were collected from the well WY 11, Qianjiang Sag, Jianghan Basin, and the sampling intervals include four of the salt cycles in the Eq3 Member of the Eogene Qianjiang Formation. Bulk geochemical data were obtained by whole rock pyrolysis, and gas chromatography-mass spectrometry (GC-MS) analyses were conducted for molecular compositions of saturated and aromatic biomarkers. Our results separated the analyzed samples into two broad categories corresponding to brackish-saline and saline lacustrine settings. Inter-salt shales deposited in the brackish-saline lakes occur over large geographic areas with relatively strong water column stratification, and are characterized by the presence of abundant gammacerane and 2, 3, 6-trimethyl-aryl isoprenoid alkanes. In contrast, inter-salt shales deposited in saline lakes tend to distribute in small areas, and the presence of abundant 3, 4, 5-trimethyl-aryl isoprenoid alkanes with lower contents of gammacerane is consistent with relatively shallow water depth. High pyrolysis S1 contents, S1/w(TOC) ratios, Ts/(Ts+Tm), and 20S/(20S+20R) and (αββ/ααα+αββ) ratios of C29 steranes are good indicators for the inter-salt shales that were deposited in the brackish-saline settings and are ideal habitats for lacustrine shale oil enrichment, since the presence of organic rich lamina favor the updip, lateral oil migration along the bedding parallel microfractures. According to the common hopane and sterane parameters as well as aryl isoprenoid biomarker distributions, it is suggested that inter-salt shale oil exploration in the Jianghan Basin should be focused on organic rich shale beds in the Eq3 and Eq4 members deposited during the maximum lake expansion. More efforts were suggested to be invested in the mature source kitchens of the Banghu Sag in addition to the continuing pilot production tests in the Wangchang area.